Investigation of Tensile and Impact Properties of Pineapple Leaf Fiber-Glass Fiber Reinforced Polymer (GFRP) Hybrid Composites - Badri, Muftil; Sari, Azzaharah Isyari Nuraini; Dalil, M; Saputra, Sukemi Indra (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
Kontes Kapal Cepat Tak Berawak Nasional (KKCTBN) held by Pusat Prestasi Nasional (Puspresnas) Kemendikbudristek RI aims to encourage innovation in the design and performance of shipping-maritime technology prototypes. The selection of the right material for the catamaran hull is very important because it affects the strength and weight of the ship. Materials such as fiber reinforced polymer, which uses glass fiber, are often used due to their good mechanical strength. However, natural fibers such as pineapple leaf fiber also have potential as composite reinforcement. The combination of natural and synthetic fibers, such as pineapple leaf fiber and glass fiber, in hybrid composites can improve the mechanical properties of the material. The purpose of this study was to investigate tensile and impact properties of pineapple leaf fiber-glass fiber reinforced polymer (GFRP) hybrid composites. Fiber preparation was carried out by separating pineapple leaf to produce fibers, alkaline treatment using 10% NaOH with a soaking time of 24 hours, and oven drying at 100?C for 60 minutes. Polymer as the matrix used was 50% while the percentage variations of pineapple leaf fiber and glass fiber were sequentially as follows 5%:45%, 10%:40% and 15%:35%. It was found that the tensile strength of the 10% pineapple leaf fiber composite was about 114 MPa and impact strength 49.96 J/mm², density 1.19 g/cm3. The results of this study indicate that the resulting composite can be used as an alternative material in the prototype hull of a catamaran type unmanned speedboat.